Gender-based violence and associated factors among women in Ethiopia: a systematic review and meta-analysis - Berhanu Wale Yirdaw; Bimrew Bayuh Yimer (BMC Women's Health)
Abstract Background Gender-based violence (GBV) is a significant public health and human rights issue globally. In Ethiopia, the true extent and associated factors of GBV among women remain inadequately synthesized. Thus, this systematic review and meta-analysis was aimed to estimate the pooled prevalence of GBV and identify its associated factors among women in Ethiopia. Methods A comprehensive search of literatures was conducted using PubMed, Medline, HINARI, EMBASE, Web of Science, Scopus, and Google scholar from November 10, 2024 to November 30, 2024 following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Additional studies were searched using a reference of identified articles. Studies reporting the prevalence of GBV and associated factors among women in Ethiopia were included. Data were extracted using a standardized form and the quality of included studies was assessed using the Newcastle-Ottawa Scale. Inspection of the Funnel plot and Egger’s test were used to evaluate the evidence of publication bias. The heterogeneity of the included studies was evaluated using Cochrane Q and I2 test. A random effects meta-analysis was computed to determine the pooled estimate of gender-based violence using STATA 17. Results A total of 19 studies with 23,787 study participants were included in this review. The meta-analysis showed that the pooled prevalence of gender-based violence among women is 51.34% (95% CI: 44.48–58.19). Factors significantly associated with GBV included monthly pocket money received from their parents, urban residence, experience of sexual intercourse, young age, alcohol consumption, being single in marital status, tight family control and number of sexual partners. Conclusion The prevalence of gender-based violence among women is found to be high, which is a significant concern. Identified associated factors highlight potential areas for targeted interventions and prevention strategies. Further research is needed to understand the complex interplay of these factors and evaluate the effectiveness of interventions. Prospero registration number CRD42024619618.